Leaf anatomical characteristics of Nepenthes species in Western Sarawak, Borneo - Mohd Hisham Nabilah Huda,; Kalu Meekiong,; Hashimah Elias, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The dimorphism and phenotypic plasticity of genus Nepenthes is taxonomically challenging. They depicted a variety of pitcher morphological features that often lead to difficulty in the species delineation. However, there is an alternative that could aid to distinguish the Nepenthes species which is by observing the anatomical characteristics of their leaves. Despite few researches had reported the comparative study on leaf anatomy of certain Nepenthes species, yet, there are very scarce data showing other distinct anatomical characteristics that could be used to differentiate the Nepenthes species especially in the western of Sarawak. Hence, this research was performed to identify anatomical characteristics that could be useful taxonomic tools for Nepenthes species identification. There are nine species with one variety and three natural hybrids were included in the study namely, Nepenthes albomarginata Lobb, N. ampullaria Jack, N. gracilis Korth, N. hirsuta Hook. f., N. hispida Beck, N. mirabilis (Lour.) Druce, N. mirabilis var. echinostoma (Hook. f.) J. H. Adam & Wilcock, N. nazreeana sp. nov. ined., N. rafflesiana Jack, N. reinwardtiana Miq., N. x trichocarpa Miq, N. x hookeriana Lindl, and N. x kuchingensis Sh. Kurata. The anatomical data of leaves, i.e stomatal complex type, stomatal size and density, type of anticlinal walls, type of glandular structures and others were analysed, tabulated and discussed.